MENATA STRATEGI REKRUTMEN TENAGA KERJA - Mohamad Muspawi (Jurnal Ilmiah Universitas Batanghari Jambi, 2018)
Recruitment is an integral part of the management of an institution or organization. Recruitment positions are quite important, because the quality of recruitment influence the quality of the performance of institutions or organizations concerned in the future. Filippo in Justine T Sirait (2006: 56) defines recruitment as an employee or prospective withdrawal of labor and the employment search process is done carefully, so as to stimulate them to want to apply for certain positions offered by the organization. Recruitment is wise when before implementation is done plannings to meet the needs of the labor or employee in an organization, what is needed and how much is needed. Once detected all necessary further carrying out the process to get the purposes of labor or employees needed. After planning labor requirements. Subsequent process is the process of opening a job. Pramana (2005: 4) says that the process of opening a job based on their workforce planning needs really been analyzed and approved by the director. Filing review of manpower requirements can be distinguished according to their needs. Selection is the process for deciding the appropriate employee from a set of candidates obtained through the recruitment process, both internal and external recruitment. In principle, the selection regardless of whether the selection made for new employees, promotion, transfer, or others, and are associated with certain stages, such as: determination of the demands of the job and the company, the determination of the type of people required, determination of tools and steps / selection procedures, factors to be considered in the selection is a tool / selection procedure, and who is doing the implementation of selection (Hariandja 2007: 125-127). The part that is no less important than recruitment is the process regarding a contract extension subcontracted employees and probation employees. Pramana (2005: 10) says that this process must be preceded by a review / assessment of employees works to the extent that their ability to carry out the duties and responsibilities of the job.Keywords: Recruitment, Manpower Professional.